PENERAPAN METODE CROSSWORD PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SMP IT AN-NAHL PERCIKAN IMAN JAMBI - Yusria; Ikram Albilal; Lusi Suswanti; Meita setya arwidya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low learning outcomes of students in the Islamic Cultural History subject. This research aims to find out (Implementation of Islamic Cultural History learning through the Crossword Puzzle learning method, improving learning outcomes through the Crossword Puzzle learning method in class VII SMP IT AN-NAHL Percikan Iman Jambi). This research is classroom action research (PTK). The subjects of this research were class VII SMP IT students with a total of 29 students. The treatment given to research subjects was to improve learning outcomes on Islamic Religious Education, material on Understanding Asmaul Husna using the Crossword Puzzle learning method. The findings of this research are as follows: The implementation of learning using the Crossword Puzzle learning method is in accordance with the learning implementation procedures. Increased class average scores on the initial test by 60,8 with a learning completion rate of 31%. In cycle I the average class score was 73.1 with a learning completeness level of 62%. And in cycle II the average score was 84.3 with learning completeness of 83% and improved student learning outcomes from the initial test to cycle II.